The Development of Textbooks in Competency-Based Indonesian Courses - Satinem Satinem; Juwati Juwati; Noermanzah Noermanzah; Santi Mariami (UNIB Press, 2023)
Indonesian language textbooks play a significant role in understanding students, especially in mastering the competence of writing scientific papers following the grammatical rules of the Indonesian language. The learning resource books used so far are still limited to theoretical studies and are not yet competency-based. For this reason, this research aims to develop competency-based textbooks on the Indonesian language at Universitas PGRI Silampari. The research uses the Dick, Carey, & Carey model. The research instruments used were needs analysis sheets, expert validation sheets, and tests. Qualitative data were analyzed by document content analysis, and quantitative data were analyzed by t-test. The results of the development of competency-based Indonesian language textbooks are feasible and effective in use, evidenced by the results of the validity test obtaining a score of 82 or 82%, meaning that the developed teaching materials are suitable for use. Then, from the results of the effectiveness test with the One Sample Test t-test, it was obtained sig (2-tailed) = 0.00, which is less than the value of 0.05, indicating that the textbook was used effectively by students.